PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PT. TEMAS TBK. PERIODE 2014-2023 - Baidawi, Muhammad; Diana, Diana; Aspiannor, Akhmad (Servqual: Jurnal Ilmu Manajemen, 2024)
Abstract Macroeconomics is one of the factors that can influence stock prices. One part of macroeconomics that can have a significant impact on company performance and stock prices is inflation, interest rates and exchange rates. The aim of this research is to analyze the influence of inflation, interest rates and exchange rates on share prices at PT. Temas Tbk. This type of research uses quantitative research. Data collection was carried out using secondary data in the form of inflation data, interest rates, exchange rates and share prices listed on the PT company website. Temas TBK. in the form of Annual Reports, Bank Indonesia (BI) and the Indonesian Stock Exchange (IDX) and the Central Statistics Agency (BPS) which is time series data for the period 2014-2023. The analysis techniques used in this research are descriptive analysis, classical assumptions, multiple linear regression, and hypothesis testing with the help of SPSS 25 software. The results of this research show that partially the Inflation variable (X1) has a significant influence on PT share prices. Temas Tbk. period 2014-2023. On the other hand, partially the variables Interest Rate (X2) and Exchange Rate (X3) do not have a significant effect on PT's share price. Temas Tbk. period 2014-2023. Meanwhile, simultaneously it shows that Inflation, Interest Rates and Exchange Rates have a significant and influential effect on PT's share price. Temas Tbk. period 2014-2023. Keywords: Inflation, Interest Rate, Exchange Rate and Stock Price